Fluxo gênico, estrutura genética espacial intrapopulacional e sistema de reprodução hierárquico entre e dentro de frutos em uma pequena população isolada de Genipa americana L., utilizando marcadores microssatélites - Manoel, Ricardo de Oliveira [UNESP] (2014)
Genipa americana L., popularly known as jenipapo is a neotropical tree species whose survival is threatened due to the processes of destruction, fragmentation and degradation of their natural habitats. To contribute to the conservation in situ and ex situ this species, the objective of this study was to investigate the genetic diversity, intrapopulation spatial genetic structure (SGS), the mating system and contemporary gene flow of G. americana in a small remnant forest (7.2 ha) located in the Mata da Figueira, in Mogi Guaçu Ecological Station, Mogi Guaçú (SP). In the population studied we found 188 adult trees and seeds were collected and sampled hierarchically within and among fruits directly from the tree canopy of 15 seed-trees on two consecutive reproductive events. Thirty-two microsatellite loci were developed and validated in 40 individuals of G. americana. Of these, seventeen were polymorphic, revealing of three to seven alleles per locus. Using the genotypes os seed-trees and progenies, was investigated Mendelian inheritance, genetic linkage and genotypic disequilibrium of six loci isolated of G. americana, not detecting genotypic disequilibrium. However, significant deviations from Mendelian segregation were found in 20.4% and 36.7 and genetic linkage between the loci in 53% and 68% of the tests performed in the reproductive events of 2010 and 2011, respectively. The average allelic richness of adults was of 8.8, for juvenile of 7.0 and seeds of 2010 and 2011, 7.2 and 8.4, respectively. The average expected heterozygosity for adults was of 0.581, for juvenile of 0.568 and seeds of 2010 and 2011, 0.576 and 0.735, respectively. The average observed heterozygosity for adults was of 0.499, for juvenile of 0.356 and seeds of 2010 and 2011, 0.476 and 0.542, respectively. The average fixation index was significantly different from zero for all samples, suggesting the occurrence of inbreeding. The multilocus crossing rate ( t m ) in ...